Consumption, Import Prices, and the Demand for Imported Consumer Durables: A Structural Econometric Investigation - Clarida, Richard H. (The Review of Economics and Statistics, 1996)
Richard H. Clarida, Consumption, Import Prices, and the Demand for Imported Consumer Durables: A Structural Econometric Investigation, The Review of Economics and Statistics, Vol. 78, No. 3 (Aug., 1996), pp. 369-374